Neologismos e desenvolvimento da competencia lexical, a partir de Querô: uma reportagem maldita - Ruy Mauricio Azevedo Morato (2012)
Really knowing a word goes far beyond of being able to infer its meaning. Using it properly requires a skill that demands a deep knowledge of lexical items by the speaker of a language. Clearly, native teachers are responsible to teach their students not only knowledge about the words often used, but also enable them to become autonomous and self-sufficient, to develop their lexical competence, in order to make them able to work with already known units, and new lexical units - the neologisms. The novel Querô uma reportagem maldita, by Plinio Marcos, enters this work to form the corpus of neologisms, since it presents a special vocabulary, possibly used by certain social groups. Later, after extracting these lexical neologisms, we highlighted some aspects related to the development of lexical competence, in order to provide useful tools to the classroom of Portuguese as mother tongue. Investigate the appearance and occurrence of neologisms, their formation processes and their use by the speakers are very important to better understand the process of lexical competence. Thus, we intend with this work, besides identifying the lexical neologisms units in the novel above, is also contributing to develop the lexical competence. The first two chapters of this dissertation deal with general aspects, justifying its development and the objectives to be achieved. The next chapter discusses the theoretical assumptions used in their construction. The fourth chapter, besides discussing the formation processes of relevant words of the neologisms found, presents them, and discusses their creation characteristics. The chapter number five is a discussion of the results from the theoretical assumptions presented. From the analysis of neologisms found, we tried to establish foundations that support the teaching of the Portuguese language lexicon. Therefore, we see how these new lexical items are an important part in vocabulary teaching, pointing the development of lexical competence.